Combat Exposure and Suicide Risk in Two Samples of Military Personnel. Issue 1 (15th October 2012) - Bryan, Craig J.; Hernandez, Ann Marie; Allison, Sybil; Clemans, Tracy
<x xml:space="preserve">Abstract</x> Objective In light of increased suicidal behaviors among military personnel and veterans since the initiation of combat operations in Afghanistan and Iraq, questions have been raised about the potential causal role of combat. The objective of the current study was to identify any direct or indirect effects of combat exposure on suicide risk through depression symptom severity, posttraumatic stress disorder (PTSD) symptom severity, thwarted belongingness, perceived burdensomeness, and fearlessness about death, consistent with the interpersonal‐psychological theory of suicide (Joiner, 2005). Method Structural equation modeling was utilized with two separate samples of deployed military personnel, 1 nonclinical (n = 348; 89.7% male, mean age = 24.50) and 1 clinical (n = 219; 91.8% male, mean age = 27.88), to test the effects of combat exposure on suicide risk. Results Greater combat exposure was directly associated with fearlessness about death and PTSD symptom severity in both samples, but failed to show either a direct or indirect effect on suicide risk. PTSD symptom severity was strongly associated with depression symptom severity, which in turn was related to suicide risk directly (in the nonclinical sample) or indirectly through low belongingness and perceived burdensomeness (in the clinical sample). Conclusions In both samples of deployed active duty military personnel, combat exposure was either unrelated to suicide risk or was too distally related to have a measurable effect. Results do not support the interpersonal‐psychological theory's hypothesis that combat exposure should be indirectly related to suicide risk through acquired fearlessness of death.